Cutting mechanics: relation to performance and anterior cruciate ligament injury risk - Havens, K. L.; Sigward, S. M. (Medicine & Science in Sports & Exercise, 2015)
Purpose: Quick changes of direction during running (cutting) are necessary for successful performance of many sports but are associated with noncontact anterior cruciate ligament (ACL) injuries. Currently, it is not known how biomechanics associated with fast performance of cutting tasks relate to the mechanics associated with increased risk for injury. Without this knowledge, the technique emphasized in injury prevention programs may be at odds with the demands of cutting tasks. The purposes of this study were to 1) identify whole body and/or joint mechanics that are related to completion times of 45° and 90° cuts and, from these variables, 2) determine which variables are predictors of performance (i.e., completion time) and/or ACL injury risk (i.e., peak knee adductor moment).